Cortical thickness and neurocognitive performance in former high-level female soccer and non-contact sport athletes - Haase, F. K.; Prien, A.; Douw, L.; Feddermann-Demont, N.; Junge, A.; Reinsberger, C. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Long-term effects of playing soccer (football) on the brain structure and function of the brain are vividly debated. While some studies showed differences in neurocognitive performance and structural brain changes in retired male players, data on female players are scarce. The present study compares cortical thickness and neurocognitive performance in former high-level female soccer (SOC) and non-contact sport athletes (CON).